Power Excel 2007 with MrExcel - Jelen, Bill.; Safari eBooks ([Indianapolis, Ind.] : Que, 2008)
"Bill Jelen ('MrExcel') presents focused, practical videos that teach you Excel 2007's best new techniques: supercharged solutions for charting, calculating, formatting, data analysis, automation, and a whole lot more! Click play to follow along as Jelen walks you through using Excel 2007's most sophisticated features... all you need to do is watch!"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed March 6, 2009).
Electronic reproduction.
Keywords: Microsoft Excel (Computer file); Business -- Computer programs; Electronic spreadsheets; Electronic books